2000
DOI: 10.1046/j.1525-1438.2000.010005372.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of urokinase-type plasminogen activator, its receptor and inhibitor type 1 in ovarian cancer

Abstract: Urokinase-type plasminogen activator (uPA), its receptor (uPAR) and inhibitor, plasminogen activator-type 1 (PAI-1) are proposed to be of prognostic significance in some cancers. To determine the prognostic value of the urokinase plasminogen activation system in ovarian cancer, levels of uPA, uPAR, and PAI-1 were measured in extracts of ovarian cancer tissue using ELISA tests. uPA and PAI-1 were determined in 70 tumor extracts and uPAR in 43 extracts. Levels were correlated with age, tumor histology, stage, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…While former studies on PAI-1 expression in OC demonstrated controversial data regarding its clinical relevance [16][17][18], however, our study significantly correlated PAI-1's expression levels with a more aggressive OC phenotype (volume of ascites, FIGO staging, lymph node status) and thus highlighting PAI-1's prognostic value. These findings are similar to those found in a re- 514 cent study of Ren et al [19], which showed PAI-1 being correlated to advanced FIGO stage, poor histological differentiation, and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 42%
“…While former studies on PAI-1 expression in OC demonstrated controversial data regarding its clinical relevance [16][17][18], however, our study significantly correlated PAI-1's expression levels with a more aggressive OC phenotype (volume of ascites, FIGO staging, lymph node status) and thus highlighting PAI-1's prognostic value. These findings are similar to those found in a re- 514 cent study of Ren et al [19], which showed PAI-1 being correlated to advanced FIGO stage, poor histological differentiation, and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 42%
“…No correlation with expression of EGFR, cathepsin-D, or c-erb B-2 was observed. 64,66,68 In the invasive cases, uPAR expression was not found to have any prognostic value for the primary tumor nor in the metastasis. 66 …”
Section: B Ovarian Cancermentioning
confidence: 87%
“…This supports the idea that uPA binds to its receptor on the surface of cancer cells increasing invasion and metastasis. 62,64 In tumors with low metastatic potential or benign tumors, the level of uPAR was significantly lower in comparison to invasive primary cancer as measured by ELISA and IHC. In addition, as with the report by Young et al 62 uPAR expression was seen in different stromal cells including endothelial cells, fibroblasts, and macrophages, but non-existent in neutrophils.…”
Section: B Ovarian Cancermentioning
confidence: 99%
“…In ovarian cancer, a strong correlation has been reported between urokinase plasminogen activator (uPA) antigen levels and poor prognosis (Konecny et al, 2001) and uPA is localised in primary and metastatic ovarian cancer specimens, as well as in the conditioned medium of many (but not all) ovarian cancer cell lines (Ahmed et al, 2002b). In addition, ovarian cancer patient's tumour fluid expresses a higher concentration of cell-free urokinase plasminogen activator receptor (uPAR) (Pedersen et al, 1993) and high levels of cell-associated uPA correlate with advance stage disease (Tecimer et al, 2000).…”
mentioning
confidence: 99%